If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(5p + 2) + -2(3 + -17p) = 3(6 + 6p) Reorder the terms: -3(2 + 5p) + -2(3 + -17p) = 3(6 + 6p) (2 * -3 + 5p * -3) + -2(3 + -17p) = 3(6 + 6p) (-6 + -15p) + -2(3 + -17p) = 3(6 + 6p) -6 + -15p + (3 * -2 + -17p * -2) = 3(6 + 6p) -6 + -15p + (-6 + 34p) = 3(6 + 6p) Reorder the terms: -6 + -6 + -15p + 34p = 3(6 + 6p) Combine like terms: -6 + -6 = -12 -12 + -15p + 34p = 3(6 + 6p) Combine like terms: -15p + 34p = 19p -12 + 19p = 3(6 + 6p) -12 + 19p = (6 * 3 + 6p * 3) -12 + 19p = (18 + 18p) Solving -12 + 19p = 18 + 18p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-18p' to each side of the equation. -12 + 19p + -18p = 18 + 18p + -18p Combine like terms: 19p + -18p = 1p -12 + 1p = 18 + 18p + -18p Combine like terms: 18p + -18p = 0 -12 + 1p = 18 + 0 -12 + 1p = 18 Add '12' to each side of the equation. -12 + 12 + 1p = 18 + 12 Combine like terms: -12 + 12 = 0 0 + 1p = 18 + 12 1p = 18 + 12 Combine like terms: 18 + 12 = 30 1p = 30 Divide each side by '1'. p = 30 Simplifying p = 30
| 3+5x=-3x-93 | | 20x+7y=3fory | | 8m-24=4 | | 6x+5=-3x+104 | | -5x+4=68+3x | | -2x+10+7x=65 | | 4+7x+x=68 | | 180=(30+x)+30+9x | | 8.5+x=7.1-x | | 62=y-19 | | x^4-8x^3+24x^2-32x=65 | | 15y-9y= | | -3-y=6 | | (40x)+(100y)=2500000 | | 2x+9=13+2x | | 15-2y/4=3 | | 2.5n-14=-12.25 | | 56-21x=-4x+29 | | 4x-8=9x+3 | | 2x-5x-7=-14 | | x+-10=12 | | -12x+10+17x-7=12+4x-2+x | | P+7=32 | | -4.9x^2-8x-30=0 | | 3a^3b-24b^4=0 | | 6k+3w-w+5k= | | 2.3x=47 | | 3m+5n=6m-2n | | 5(2)+15x=10 | | 21x^2-6x+13=0 | | x^2+9y^2=28 | | 3x+2-x-5=7x+6-4x-2 |